2022
DOI: 10.1007/s00267-022-01593-z
|View full text |Cite
|
Sign up to set email alerts
|

How much Fear? Exploring the Role of Integral Emotions on Stated Preferences for Wildlife Conservation

Abstract: Scientific evidence suggests that emotions affect actual human decision-making, particularly in highly emotionally situations such as human-wildlife interactions. In this study we assess the role of fear on preferences for wildlife conservation, using a discrete choice experiment. The sample was split into two treatment groups and a control. In the treatment groups the emotion of fear towards wildlife was manipulated using two different pictures of a wolf, one fearful and one reassuring, which were presented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…This finding suggests that socio‐demographic parameters have idiosyncratic and context‐specific effects on attitudes. Similarly, although we expected to find important effects of regional factors on attitudes (Arbieu et al., 2019; Karlsson & Sjöström, 2007; Notaro & Grilli, 2022), only the distance to the closest wolf territory affected attitudes towards wolves. These results reinforce the strength of emotional factors in shaping attitudes towards wolves, with important implications for wolf conservation and the management of social conflicts.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This finding suggests that socio‐demographic parameters have idiosyncratic and context‐specific effects on attitudes. Similarly, although we expected to find important effects of regional factors on attitudes (Arbieu et al., 2019; Karlsson & Sjöström, 2007; Notaro & Grilli, 2022), only the distance to the closest wolf territory affected attitudes towards wolves. These results reinforce the strength of emotional factors in shaping attitudes towards wolves, with important implications for wolf conservation and the management of social conflicts.…”
Section: Discussionmentioning
confidence: 79%
“…Understanding these relations is therefore important in a context of human‐wildlife coexistence because emotions are expected to influence behaviours (Lerner et al., 2015) and decision‐making (Ghasemi et al., 2021; Wieczorek Hudenko, 2012). For instance, negative emotions have been shown to affect willingness to pay for wolf protection, and these relations between emotions and attitudes are modulated by contextual situations (Notaro & Grilli, 2022). However, we still have a limited understanding of the differential effects of other emotional states like joy, interest or anger on attitudes and we can reasonably expect diverging strategies for managing human‐wildlife encounters and coexistence in fear‐, anger‐, or joy‐dominated contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, research on immediate emotions generally have participants engage in tasks that activate their decision-making processes; this is done to accommodate the fact that immediate emotions are experienced during decision-making (Schlösser et al, 2013). For example, Notaro and Grilli's (2022) inquiry on how emotions shape public preferences for wildlife conservation had participants choose between different monetary amounts that they would donate to conservation efforts (Notaro and Grilli, 2022). It is also common for affective research to ascertain participants' immediate emotions via objective physiological measures, which is feasible given that immediate emotions are actually experienced (Schlösser et al, 2013).…”
Section: Category Description Example With Potential Behavioral Conse...mentioning
confidence: 99%
“…• Participants are presented with various pro-environmental options and instructed to decide as if their selection was binding (Notaro and Grilli, 2022).…”
Section: Suggested Research Protocol Example Set Upmentioning
confidence: 99%
“…Attention, attitude, and relative interest are predominantly affective domains, while knowledge is purely cognitive. In this paper, we implicitly and explicitly investigated the three affective domains because of their crucial role in nature conservation [39][40][41][42][43][44][45]. It is suggested that organisms which capture human attention (e.g., by colour) also enhance their willingness to protect them [41,46,47].…”
Section: Introductionmentioning
confidence: 99%